HUKUM WARIS ADAT MANGGARAI DAN HUKUM WARIS DALAM HUKUM POSITIF DARI PERSPEKTIF KESETARAAN GENDER - Yeyen Andaru, Viktoria; Jemarut, Wihelmus (LPPM Universitas Bina Bangsa, 2025)
The customary inheritance law system in Indonesia regulates the distribution of inheritance based on local cultural norms. In regions like Manggarai, East Nusa Tenggara, the dominant patrilineal system causes gender inequality in inheritance distribution, prioritizing male heirs while females receive only symbolic gifts. Although Indonesia's positive law guarantees equal inheritance rights, customary practices that favor males hinder the effective implementation of gender equality. This qualitative study, using document analysis, in-depth interviews, and participatory observation, explores the interaction between customary and positive law and the application of gender equality in inheritance. The findings reveal a tension between male-preference cultural norms and the gender equality principles in positive law. Achieving better gender equality in inheritance requires collaboration between the government, customary communities, and legal institutions, along with effective socialization of women's rights in both legal systems to ensure fairer and more equitable inheritance distribution.